Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/cancers11050662
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Pattern of Mesothelial-Mesenchymal Transition Induced in the Normal Peritoneal Mesothelium by High-Grade Serous Ovarian Cancer

Abstract: The study was designed to establish whether high aggressiveness of high-grade serous ovarian cancer cells (HGSOCs), which display rapid growth, advanced stage at diagnosis and the highest mortality among all epithelial ovarian cancer histotypes, may be linked with a specific pattern of mesothelial-mesenchymal transition (MMT) elicited by these cells in normal peritoneal mesothelial cells (PMCs). Experiments were performed on primary PMCs, stable and primary ovarian cancer cells, tumors from patients with ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Moreover, we previously reported compression-induced changes in OvCa multicellular aggregates correlated with upregulation of epithelial-mesenchymal transition (EMT)-associated genes 11 . Together these data suggest that ascites-induced compression may play a role in mesothelial-mesenchymal transition 21 , 44 . A limitation of the current study is the lack of information regarding the uniformity of ascites-induced compression throughout structures of the peritoneal cavity impacted by OvCa metastases.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, we previously reported compression-induced changes in OvCa multicellular aggregates correlated with upregulation of epithelial-mesenchymal transition (EMT)-associated genes 11 . Together these data suggest that ascites-induced compression may play a role in mesothelial-mesenchymal transition 21 , 44 . A limitation of the current study is the lack of information regarding the uniformity of ascites-induced compression throughout structures of the peritoneal cavity impacted by OvCa metastases.…”
Section: Discussionmentioning
confidence: 67%
“…S3c). While mesenchymal transition of OvCa cells was reported to be caused by several soluble growth factors, 23 this finding indicates that an adhesive molecule may also greatly influence the mesenchymal characteristics of OvCa cells.…”
Section: Ocams Interact With Ovca Cells To Create a Permissive Tumormentioning
confidence: 96%
“…This mesenchymal change in MCs may have been caused by the release of a soluble growth factor from cancer cells as specific studies have already reported that a variety of factors collected from the conditioned media used to culture OvCa cells induced mesenchymal changes in MCs. 23 Notably, TGF-β1 has been recognized as one of the most common mesenchymal inducers of MCs. 16,19,30 An average of 4.62 ng/ml (range: 0.38-22.34 ng/ml) of TGF-β1 was detected in the ascites of patients with malignant ovarian tumors ( Fig.…”
Section: Ocams Interact With Ovca Cells To Create a Permissive Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior studies had found multiple genes and signaling pathways participated or play dominant role in tumorigenic process of gastric cancer, such as HGF, which secreted by cancer-associated fibroblasts, could promote vascularization in gastric cancer via activating PI3K/Akt and ERK1/2 signaling pathway [2], and accelerated proliferation, migration and invasion of MET-unamplified gastric cancer cells through activating c-MET/Stat3/twist1 signaling pathway [3]. It was noteworthy that HGF-c-MET signaling pathway is activated in a range of cancer types including gastric cancer, colorectal cancer, head and neck cancer, hepatocellular carcinoma, lung cancer, urothelial carcinoma of bladder, glioblastoma, melanoma and ovarian cancer, among others [2,[4][5][6][7][8][9][10][11], and associated with an aggressive phenotype and poor prognosis in pancreatic cancer [12].…”
Section: Introductionmentioning
confidence: 99%